Enzymic hydrolysis of proteins from aristichthys nobilis by protease P 'Amano' 3 - Yu, Swee Yean; S., Fazidah (John Wiley & Sons, 1994)
Proteins from Aristichthys nobilis were hydrolysed using Protease P 'Amano' 3. A degree of hydrolysis (d.h.) of 15% was obtained with an enzyme:substrate concentration of 2%, after 3 h of hydrolysis. Nitrogen recovery was 60%. The hydrolysate had a moisture content of 3·0%, protein 87·0%, fat 0·85% and ash 8·65%. The amounts of all the amino acids analysed increased after hydrolysis. Bitterness was detected after 3 h of hydrolysis.